2019
DOI: 10.2478/msr-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Quality of One-channel Telemetric ECG Sensor Signal in Maximum Exercise Stress Tests

Abstract: The aim of this study was to evaluate the quality of the ECG signal, obtained from a telemetric body-sensor device during a maximum stress test on an ergometer. Twenty-three subjects, 13 males, were included in the study (20.56±1.19 years). Two different sensor positions were verified on each subject by the concurrent use of two ECG sensors. Each subject participated in four exercise stress tests: two on a treadmill and two on a cycle ergometer. In the first test, both sensors were attached to self-adhesive sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Sensor from the present study was previously used during EST in laboratory conditions with the same type of fixation and used electrodes [18]. The additional fixation of the sensor with self-adhesive tapes at position LI showed improvement of the signal quality on the treadmill up to the level of 97.64 %, while on a cycle ergometer the signal was acceptable at the 100 % level.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Sensor from the present study was previously used during EST in laboratory conditions with the same type of fixation and used electrodes [18]. The additional fixation of the sensor with self-adhesive tapes at position LI showed improvement of the signal quality on the treadmill up to the level of 97.64 %, while on a cycle ergometer the signal was acceptable at the 100 % level.…”
Section: Discussionmentioning
confidence: 75%
“…Recent studies showed that the wireless body ECG sensor is a feasible solution for reliable and accurate long-term heart rhythm monitoring, but the sensor placement and fixation is an important factor which can influence the signal quality and needs to be taken into consideration [18], [19], [20]. Accordingly, our main goal was to define whether it is possible to measure quality electrocardiographic report using an ECG body-sensor during standardized outdoor tests.…”
Section: Introductionmentioning
confidence: 99%
“…The process was repeated for the last two days on the other device. It was reported in [39] that the signal quality obtained using both fixed and non-fixed sensors was good at the LI position. The signal quality of the data from the LS position was less acceptable than the signal quality of the data from the LI position due to the influence of shoulder movement, particularly during the treadmill EST.…”
Section: Ref Research Designmentioning
confidence: 94%
“…However, the study included only two pregnant women. Širaiy et al (2019) [39] studied the applicability of ECG measurements for monitoring heart rhythm during the conduction of intensive activity. Aiming at evaluating ECG distortion levels in relation to the sensor position and fixation method, twenty-three participants conducted a total of four exercise stress tests (EST) during four days, i.e., two while cycling on an ergometer and two while running on a treadmill.…”
Section: Ref Research Designmentioning
confidence: 99%
“…Significant advances in the prevention of cardiovascular accidents would become possible if the ECG could be measured during regular sports activities. The study in [25] was testing the applicability of ECG measurements for rhythm monitoring during intensive activity, i.e., cycling on ergometer and running on a treadmill according to the RAMP protocol [26]. Two different positions and two different fixation methods of the electrodes have been tested on 23 participants.…”
Section: Sports/fitness Measurementsmentioning
confidence: 99%